A Guide to Developing Multicultural, Nonsexist Education Across the Curriculum - Iowa State Dept. of Education, Des Moines; Iowa State Dept. of Education, Des Moines ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This guide is designed to help administrators and teachers develop curriculum and improve instruction in multicultural, nonsexist education in response to a 1985 mandate from the Iowa State Assembly requiring the coordination of curriculum across subject matter lines at all levels of education. Multicultural, nonsexist education (MCNSE) is a process through which a body of knowledge and a set of attitudes and skills are infused throughout the curriculum. The purpose of this guide is to infuse MCNSE goals, objectives, strategies, and evaluation across the K-12 curriculum. The following topics are included: (1) rationale; (2) Iowa law and school standards; (3) teacher strategies and classroom examples for incorporating student goals and objectives into each vertical strand of the curriculum; and (4) evaluation. The following content areas are discussed: (1) Arts; (2) Foreign Language; (3) Health and Physical Education; (4) Language Arts; (5) Mathematics; (6) Science; (7) Social Studies; and (8) Vocational Education. A glossary, an evaluation checklist, a 107-item annotated bibliography of resources on theory and classroom applications, and a list of resource organizations are appended. (FMW)
Administrators.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cultural Awareness; Elementary Secondary Education; Intercultural Programs; Interdisciplinary Approach; Multicultural Education; Nondiscriminatory Education; Sex Fairness; State Curriculum Guides; State Programs; Iowa; Guides, Non-Classroom.